KAJIAN NORMA PANCASILA TERHADAP PENERAPAN SANKSI PIDANA MATI DALAM HUKUM POSITIF DI INDONESIA - Rangkuti, Irvino (Res Nullius Law Journal, 2023)
Pancasila's life vision is based on the fact that the universe and all the harmony in it were created by God Almighty. There is nothing in the universe that is different in composition from other universes. Maintaining order means upholding human dignity so that Pancasila has a legal reference for self-protection in the passive and active sense. The subject of the death penalty has become the concern of criminal law experts, criminologists, and victimologists, especially related to the philosophy of punishment, according to which the purpose of punishment is not only to frighten the convict but also to attract attention. Basically certain qualifying activities are activities that directly violate human dignity and/or endanger the existence of human society. Therefore, the purpose of capital punishment is only to prevent other people from committing acts that lead to the imposition of capital punishment. The death penalty in Indonesia is still required for serious crimes, including premeditated murder, those guilty of genocide and crimes against humanity, drug dealers, high-level corruption, and terrorists. The position of the Special Criminal Law in the criminal justice system complements the criminal law codified in the Criminal Code in terms of increasing the threat of punishment for crimes that threaten the implementation of clothing and food facilities; Law Number 21 of 1959 (Prp) concerning Threats of Economic Crimes; Atomic Energy Regulation No. 31 of 1964.